Uncovering bighorn sheep life-history trajectories in multidimensional trait space - Benjamin Larue; Fanie Pelletier; Marco Festa-Bianchet; Sandra Hamel (Proceedings of the National Academy of Sciences, 2025)
Individual heterogeneity shapes ecoevolutionary processes at multiple scales. Yet, the scarcity of long-term life-history data and limitations in classic statistical tools hinder our capacity to uncover and understand individual heterogeneity in wildlife populations. Here, we apply an underused multivariate statistical method to uncover four heterogenous life-history trajectories in wild female bighorn sheep ( Ovis canadensis ). Remarkably, these trajectories had remained unobserved in the population despite nearly five decades of monitoring. Our results indicate substantial among-trajectory heterogeneity in growth, senescence, life history trade-offs, fitness, and contributions to population growth. Some trajectories suggest the presence of life history trade-offs while others include silver spoon effects, leading to heterogenous life-history outputs. Then, we show that mother identity and year of birth are relatively good predictors of heterogeneity, indicating that individual trajectories could be largely set during early life. Critically, our results demonstrate that heterogeneity in life-history trajectories can be inconspicuous, yet substantial and structured across multiple traits within a population. Uncovering and understanding this heterogeneity in other wild populations will be key to advancing our knowledge of ecoevolutionary processes across populations and species.